2018
DOI: 10.1016/j.addbeh.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity components in relation to alcohol and cannabis use, motives, and problems in treatment-seeking cigarette smokers

Abstract: Anxiety sensitivity (AS)- fear of anxiety symptoms and their potential negative consequences-has been implicated in the development of substance use problems and motivation to use substances for coping with distress, though the AS components (physical, cognitive, and social concerns) have not been studied extensively in relation to alcohol- and cannabis-related variables. In a cross-sectional design, self-report measures of AS and alcohol and cannabis use, motives, and problems were administered to 364 treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 75 publications
(101 reference statements)
5
13
1
Order By: Relevance
“…Indeed, though several studies have reported a relation between AS and greater alcohol consumption (Cox, Swinson, Shulman, Kuch, & Reichman, 1993;Lammers, Kuntsche, Engels, Wiers, & Kleinjan, 2013;Paulus, Manning, et al, 2017;Stewart, Peterson, & Pihl, 1995;Stewart, Zvolensky, & Eifert, 2001), the large majority of studies have not found evidence of an association between AS and greater alcohol consumption (Buckner, Bonn-Miller, Zvolensky, & Schmidt, 2007;Chavarria et al, 2015;Guillot et al, 2018;Johnson et al, 2008;Leyro, Zvolensky, Vujanovic, & Bernstein, 2008;Novak, Burgess, Clark, Zvolensky, & Brown, 2003;Paulus, Valadka, et al, 2017;Paulus, Vujanovic, & Wardle, 2016;Woicik, Stewart, Pihl, & Conrod, 2009;Zvolensky et al, 2007), including the current study. Also concordant with this possibility, the evidence for an association between AS and hazardous drinking (AUDIT total scores) has been mixed, with some studies reporting evidence of this association (Guillot et al, 2018;Paulus, Manning, et al, 2017;Zvolensky et al, 2019;Zvolensky et al, 2014) and other studies not finding evidence of this association (Bakhshaie, Zvolensky, Allan, Vujanovic, & Schmidt, 2015;Haas et al, 2019;Paulus, Valadka, et al, 2017;Zvolensky, Kotov, Antipova, & Schmidt, 2003), including the current study. In contrast, AS consistently has been related to greater alcohol problems (Chavarria et al, 2015;Guillot et al, 2019;Guillot et al, 2018;Lammers et al, 2013;Paulus, Manning, et al, 2017;Paulus et al, 2016;Schmidt, Buckner, & Keough, 2007;…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Indeed, though several studies have reported a relation between AS and greater alcohol consumption (Cox, Swinson, Shulman, Kuch, & Reichman, 1993;Lammers, Kuntsche, Engels, Wiers, & Kleinjan, 2013;Paulus, Manning, et al, 2017;Stewart, Peterson, & Pihl, 1995;Stewart, Zvolensky, & Eifert, 2001), the large majority of studies have not found evidence of an association between AS and greater alcohol consumption (Buckner, Bonn-Miller, Zvolensky, & Schmidt, 2007;Chavarria et al, 2015;Guillot et al, 2018;Johnson et al, 2008;Leyro, Zvolensky, Vujanovic, & Bernstein, 2008;Novak, Burgess, Clark, Zvolensky, & Brown, 2003;Paulus, Valadka, et al, 2017;Paulus, Vujanovic, & Wardle, 2016;Woicik, Stewart, Pihl, & Conrod, 2009;Zvolensky et al, 2007), including the current study. Also concordant with this possibility, the evidence for an association between AS and hazardous drinking (AUDIT total scores) has been mixed, with some studies reporting evidence of this association (Guillot et al, 2018;Paulus, Manning, et al, 2017;Zvolensky et al, 2019;Zvolensky et al, 2014) and other studies not finding evidence of this association (Bakhshaie, Zvolensky, Allan, Vujanovic, & Schmidt, 2015;Haas et al, 2019;Paulus, Valadka, et al, 2017;Zvolensky, Kotov, Antipova, & Schmidt, 2003), including the current study. In contrast, AS consistently has been related to greater alcohol problems (Chavarria et al, 2015;Guillot et al, 2019;Guillot et al, 2018;Lammers et al, 2013;Paulus, Manning, et al, 2017;Paulus et al, 2016;Schmidt, Buckner, & Keough, 2007;…”
Section: Discussioncontrasting
confidence: 73%
“…In particular, AS has been associated with both SU coping expectancies and motives (i.e., both expecting a substance to reduce NA if used and explicitly reporting the reason for using a substance is to reduce NA, respectively) in regard to cigarette smoking and alcohol and cannabis use (DeMartini & Carey, 2011; Guillot et al, 2019; Guillot, Blumenthal, Zvolensky, & Schmidt, 2018; Guillot, Leventhal, Raines, Zvolensky, & Schmidt, 2016). AS additionally has been associated with problems related to the use of various substances, including tobacco, alcohol, and cannabis (Guillot et al, 2019; Guillot et al, 2018). More specifically in regard to cigarette smokers, AS has been prospectively associated with more intense tobacco withdrawal and higher risk of smoking lapse and relapse (Bakhshaie et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Future work may benefit from examining other potential moderators of PFI outcomes. For example, certain types of anxiety (e.g., social anxiety) and anxiety-related constructs (e.g., fear of physical or cognitive symptoms of anxiety) have been differentially related to cannabis-related problems by gender (Buckner, Zvolensky, & Schmidt, 2012; Guillot, Blumenthal, Zvolensky, & Schmidt, 2018), suggesting that observed differences in cannabis-related problems may be partially influenced by demographic factors (e.g., gender) and psychological factors such as anxiety and anxiety-related constructs.…”
Section: Discussionmentioning
confidence: 99%
“…These results strongly suggest that administration of cannabis and alcohol may additively enhance DA release the NAc. Guillot et al [200] showed that, among people using cannabis and alcohol, the interplay between social anxiety and coping-oriented motives for using one substance (such as cannabis or alcohol) may pose difficulties in refraining from other substances such as alcohol or tobacco). Therefore, it is important to tailor multi-substance treatments to specific needs when a single-substance intervention may not be effective.…”
Section: Specific Alcohol-drug Interactionsmentioning
confidence: 99%